PERAN STEK DAUN DALAM MENINGKATKAN KUALITAS PRODUKSI TEH (Camellia sinensis O.K) THE FUNCTION LEAFCUT METHODE FOR INCREASING QUALITY TEA PRODUCTION - Subantoro, Renan (MEDIAGRO, 2005)
Tea is one of crops plantation has economics high value from agriculture sector. Thus, Government always tried to increase tea production through research in the cultivation  tecnics. Crops reproduction through vegetatif leafcut is methode could increase quality and quantity tea production. Succesful leafcut methode effected internal and external factor. Internal factor is cutleaf material, and external factor is environment to influence of growth and development leafcut.   Key words :   Quantity dan Quality Tea Production, Leafcut  methode, internal factors, exsternal factors,